The economy as cultural system : theory, capitalism, crisis - Dufresne, Todd, 1966-; Sacchetti, Clara (New York, NY : Continuum International Pub., 2013)
'The 2008 global crisis, unemployment, lack of retirement funds, bank bailouts... today, the'economy' is on everyone's mind. But what makes this rather opaque concept work? This collection of essays seeks out the answer by exploring contemporary capitalism from a variety of theoretical perspectives and by confronting the economy as a cultural system, a theory, and a driving force of every day life in the West.
The first part of the book discusses past and present representation of capitalism (from Hegel and Marx to Negri and Florida) along with their continuing impact. The second part focuses on capitalism as a locus of power and resistance, and maps possible responses to the current situation. The roles of metaphor and discourse is examined throughout to rethink the implications of power in the context of globalization and consumer culture.
Each chapter features an abstract, study questions, as well as further reading suggestions, which, along with its accessible theoretical coverage, will make the book an essential study tool for students in social and political thought, globalization, and social theory.'--pub. desc.
Includes bibliographical references (p. [177]-193) and index.
Keywords: Capitalism -- Social aspects -- History -- 21st century; Global Financial Crisis, 2008-2009.; Economic development